Contemporary art museum (Agargaon, Sher E Bangla Nagar, Dhaka) - Soha, Dilshad Samina (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2013.